Cardiovascular Risk Factor Profile of Unstable angina patients in Bangladesh - Siddique, MA; Sultan, MA; Rahman, MA; Parvin, T; Jamil, AA; Haque, S (Nepalese Heart Journal, 2004)
In recent years, unstable angina has emerged as a dominant cause of hospital Admission.